Hambatan Implementasi E-Modul Pembelajaran IPAS Materi Sistem Pernapasan Manusia di Kelas V MIS Kajai Talamau (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze various obstacles in the implementation of e-modules in the Integrated Science (IPAS) subject, particularly on the topic of the human respiratory system in Grade V at MIS Kajai Talamau. The main focus of this study is to explore the gap between the potential of digital innovation and the reality of infrastructural constraints in elementary schools. This study employs a qualitative approach with a case study design. The research subjects include fifth-grade teachers and students, with data collection techniques consisting of observation, in-depth interviews, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results indicate that although digital media has the potential to enhance learning motivation, its implementation still faces significant challenges. The main obstacles include psychological factors and teachers’ readiness in dealing with high administrative workloads, as well as students’ economic limitations and accessibility. In addition, the lack of technical support and the limited availability of high-quality digital resources constitute significant barriers to the effectiveness of e-modules. As a solution, this study recommends the need for equitable technology policies, intensive digital skills training for both teachers and students, the implementation of interactive learning, and the provision of digital resources to ensure equitable access to education across various regions in Indonesia